Variations of Models and Learning Platforms for Prospective Teachers During the COVID-19 Pandemic Period - Gunawan Gunawan; Ni Made Yeni Suranti; Fathoroni Fathoroni (Indonesian Journal of Teacher Education, 2020)
The application of social distancing by the government has a significant impact on learning activities in tertiary institutions. Colleges divert class meetings with online meetings in networking and home assignments. This study aims to describe the variation of models and platforms used in online learning for prospective teachers during the social distancing period. This research was conducted through a survey and focus group discussion (FGD) conducted online to obtain information about the implementation of learning, applications used, constraints during learning, how to deliver material, and the number of meetings held weekly. Survey data and FGDs obtained were analyzed descriptively. The survey results show that all lecturers carry out online learning during the COVID-19 prevention period. Most lecturers organize learning and discussion through social media applications such as WhatsApp. Submission of material is mostly done by sharing files through WhatsApp messages and other social media. The most common obstacle that arises during the implementation of online learning is the limited internet access by lecturers and student teacher candidates. Learning is carried out in both categories with an average number of online meetings twice a week according to the credits of each lecture.